2016
DOI: 10.4191/kcers.2016.53.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Strength Development of Alkali-Activated Fly Ash Exposed to a Carbon Dioxide-Rich Environment at an Early Age

Abstract: The development of a binder system with a lower carbon footprint as an alternative to Portland cement has been intensely researched. In the present study, alkali-activated fly ash exposed to carbon dioxide at an early age was characterized in compressive strength tests and by MIP, XRD and FT-IR analyses. The compressive strength of carbonated specimens experienced a dramatic increase in comparison to uncarbonated specimens. The microstructural densification of the carbonated specimens was evidenced by MIP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The obtained results provide new insight into the chemistry of aluminosilicate gel exposed to a CO 2 -rich environment at an early age, and explain the strength enhanced by exposure to a CO 2 -rich environment observed in a recent work conducted by the authors [12]. It should be noted that the compressive strength of AFA exposed to conditions identical to the present study can be found in [12].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The obtained results provide new insight into the chemistry of aluminosilicate gel exposed to a CO 2 -rich environment at an early age, and explain the strength enhanced by exposure to a CO 2 -rich environment observed in a recent work conducted by the authors [12]. It should be noted that the compressive strength of AFA exposed to conditions identical to the present study can be found in [12].…”
Section: Discussionsupporting
confidence: 82%
“…It should be noted that the compressive strength of AFA exposed to conditions identical to the present study can be found in [12]. Firstly, the main gel constituents Si and Al behaved differently, while Na was in close proximity to Al.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations